Investigation of Photon Radiation Attenuation Capability of Different Clay Materials - Mohamed Elsafi (MDPI AG, 2021)
This work aims to experimentally report the radiation attenuation factors for four different clays (red, ball, kaolin and bentonite clays) at four selected energies (emitted from Am-241, Cs-137, and Co-60). The highest relative difference in the mass attenuation coefficient (MAC) is equal to −3.02%, but most of the other results are much smaller than this value, proving that the experimental and theoretical data greatly agree with each other. From the MAC results, the shielding abilities of the clay samples at 0.060 MeV follow the order of: bentonite > red > ball > kaolin. Thus, at low energies, the bentonite clay sample provides the most effective attenuation capability out of the tested clays. The half value layer (HVL) increases as energy increases, which suggests that, only a thin clay sample is needed to sufficiently absorb the radiation at low energies, while at higher energies a thicker sample is needed to shield the same amount of high energy radiated. Furthermore, bentonite clay has the lowest HVL, while the kaolin clay has the greatest HVL at all energies. The radiation protection efficiency (RPE) values at 0.060 MeV are equal to 97.982%, 97.137%, 94.242%, and 93.583% for bentonite clay, red clay, ball clay, and kaolin clay, respectively. This reveals that at this energy, the four clay samples can absorb almost all of the incoming photons, but the bentonite clay has the greatest attenuation capability at this energy, while kaolin clay has the lowest.